An enterprising municipality? Municipalisation, corporatisation and the political economy of Birmingham City Council in the nineteenth and twenty-first centuries. Issue 6 (2nd November 2017) - Skelcher, Chris
ABSTRACT: English local authorities not only have a high level of path dependency but also are capable of significant path-breaking innovations. Conventional 'great man' and punctuated equilibrium explanations of path-switching undervalue material factors. Theoretical sampling is used to develop and illuminate the way in which material conditions impact two significant changes in the institutional path of Birmingham City Council – the late nineteenth-century municipalisation of private providers (gas and water) and the early twenty-first century corporatisation of public services (back-office functions, building control, educational support, and museums and art galleries). Data are drawn from secondary sources including Council documents and contemporary accounts. Centrifugal pressure in the early twenty-first century result in arm's length companies offering greater financial resilience. This contrasts with late nineteenth-century centripetal pressure to minimise the patchwork of private providers and trade for a wider public benefit.